2021
DOI: 10.3390/biology10111214
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profile of New Gene Markers Encoding Proteins Responsible for Structure of Porcine Ovarian Granulosa Cells

Abstract: The extracellular matrix (ECM) in granulosa cells is functionally very important, and it is involved in many processes related to ovarian follicle growth and ovulation. The aim of this study was to describe the expression profile of genes within granulosa cells that are associated with extracellular matrix formation, intercellular signaling, and cell–cell fusion. The material for this study was ovaries of sexually mature pigs obtained from a commercial slaughterhouse. Laboratory-derived granulosa cells (GCs) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 104 publications
2
16
0
Order By: Relevance
“…And the THBS2 and THBS4 are grouped in the same class as they show high structural homology. In present study, genes involved in the ECM-receptor interaction of the thyroid that encode extracellular matrix components were up-regulated ( LAMA3, CHAD, THBS2, THBS4 ), may directly affects BP within the ovary, such as folliculogenesis, ovulation, and steroidogenesis ( Kulus et al, 2021 ). In a study on bovine corpus luteum, the ECM-receptor interaction was identified to be important in controlling ovarian cell development and function ( Kliem et al, 2007 ), which is consistent with our findings in the pathway.…”
Section: Discussionmentioning
confidence: 60%
“…And the THBS2 and THBS4 are grouped in the same class as they show high structural homology. In present study, genes involved in the ECM-receptor interaction of the thyroid that encode extracellular matrix components were up-regulated ( LAMA3, CHAD, THBS2, THBS4 ), may directly affects BP within the ovary, such as folliculogenesis, ovulation, and steroidogenesis ( Kulus et al, 2021 ). In a study on bovine corpus luteum, the ECM-receptor interaction was identified to be important in controlling ovarian cell development and function ( Kliem et al, 2007 ), which is consistent with our findings in the pathway.…”
Section: Discussionmentioning
confidence: 60%
“…LAMB1 participates in follicle development and indirectly affects the secretion of estradiol in follicles ( Kulus et al, 2021 ). Phosphorylation sites in LAMB1 play a regulatory role over protein function, LAMB1 promotes protein phosphorylation and influence protein structure, and protein tertiary structure in turn affects the spatial structure of TEY and improves GUM ( Kulus et al, 2021 ). The ERGIC2 protein is an endoplasmic reticulum resident protein ( Yu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular matrix is present in all organs and tissues and is a mixture of cellular and non-cellular components that can regulate a variety of cellular processes [ 71 ]. It was shown that the extracellular matrix is a major component of the ovarian matrix and can mediate many physiological functions in the ovary, such as follicular growth and development, ovulation, and steroidogenesis [ 72 ]. The enrichment of the extracellular matrix is consistent with a recent report on Nandan-Yao domestic chickens [ 73 ].…”
Section: Discussionmentioning
confidence: 99%